Shoot regeneration in Nepenthes mirabilis as affected by flurprimidol and GA3 application - MURNI DWIATI; PUDJI WIDODO; AGUS HERY SUSANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Dwiati M, Widodo P, Susanto AH. 2023. Shoot regeneration in Nepenthes mirabilis as affected by flurprimidol and GA3 application. Biodiversitas 24: 4168-4174. Nepenthes mirabilis (Lour.) Druce. is a pitcher plant species at a higher risk of extinction mainly due to overexploitation. Previous investigations have shown that in vitro micropropagation can be used as an approach for ex-situ conservation of N. mirabilis. Therefore, this study aimed to assess the new shoot formation of N. mirabilis under in vitro conditions stimulated with the application of flurprimidol and GA3. The three concentrations of flurprimidol and GA3 used as treatments were arranged factorially in a Randomized Complete Block Design (RCBD), with internodes 2, 3, 4, and 5 serving as blocks. Based on the results, F1G0 (flurprimidol of 1 mgL-1 without GA3) had the highest shoot formation, which was not accompanied by sufficiently high contents of chlorophyll, leading to improper shoot development. Despite the smaller number of newly formed shoots in F2G2 (flurprimidol of 2 mgL-1 and GA3 of 2 mgL-1), significantly higher chlorophyll contents were observed, enabling better development of shoot. Leaf length and shoot diameter also showed similar results under F2G2, indicating that higher concentrations of exogenous GA3 were necessary for better shoot development. This indicated that appropriate concentrations of both plant growth regulators should be applied for micropropagation of N. mirabilis in support of ex-situ conservation.